Kritisasi Anakronisme Arkoun terhadap Keislaman dan Kemodernan - Nurkhalis, Nurkhalis; Misbah, T. Lembong (Jurnal Pemikiran Islam, 2023)
Arkoun tried to suggest or introduce anachronistic as the beginning of the new Islamic model era. The representative Arab world of Islam does not recognize the world of anachronisms to accept the presence of the activities and creativity of modernity today. The essence of modernity is in fact necessary only in the methodology of open-minded Islamic societies, not converting Muslims to the Islamic worldview. Rethinking, reconstruction and renewal in the modern era are regarded as Islamic opposition due to the application of anachronisms changing the new order of Islam. Anachronism aims to devour Islamic turats (Islamic traditions) but is trapped in Islamic criticism. Islam Kaffah (Islamic perfectionist) will be brought into Islam al-yassar (Islamic Left). An anachronistic deliberation of the approaches used in the past issue of excavation of legal finalization will change according to modernity. Anachronism have been placed modernity as the creation of the advancement of all sides of human life with unlimited activities, creativity and ethos.AbstrakArkoun mencoba mensugestikan atau memperkenalkan anakronistik sebagai dimulainya era model Islam baru. Dunia Arab yang representatif Islam tidak mengenal adanya dunia anakronisme untuk menerima kehadiran aktifitas dan kreatifitas modernitas sekarang. Essensi modernitas sejatinya dibutuhkan hanya dalam metodologi membuka akal masyarakat Islam, bukan mengubah Muslim terhadap worldview Islam. Rethinking, rekonstruction dan renewal di era modern dianggap sebagai oposisi Islam akibat aplikasi anakronisme merubah tatanan baru keIslaman. Anakronisme bertujuan membaguskan turats Islam (tradisi Islam) namun terjebak dalam kritik Islam. Islam kaffah akan digiring ke dalam Islam al-yassar (Islam Kiri). Delibrasi anakronistik terhadap pendekatan-pendekatan yang digunakan pada masalah lalu tersebut tentang penggalian finalisasi hukum akan berubah sesuai modernitas. Anakronisme menempatkan modernitas sebagai penciptaan kemajuan semua sisi kehidupan manusia dengan berbagai aktifitas, kreatifitas dan ethos yang tanpa batas.